New media and technologies are change teaching and learning chemistry - Rizman Herga, Nataša; Dinevski, Dejan (Anali PAZU, 2022)
Learning and teaching chemistry is a complex process because it involves abstract concepts that can not often be seen or touched. The use of modern information technologies offers assistance in overcoming such problems as it enables visualization of natural phenomena that are too small, too fast, abstract or too enormous to be directly observed. Numerous studies show that the use of visualization materials (from physical models, analogies, animations, simulations, submicropresentations, virtual environments) improves the understanding of chemical concepts. Visualization of abstract concepts and safe environment for experimentation are only two reasons pointing in favor of the use of ICT in teaching chemistry. We wanted to explore whether the Slovenian teachers include it when teaching chemistry and how often individual materials for visualization are included. The aim of this paper is to analyze the use of visualization elements enabled by ICT in teaching chemistry among Slovenian primary school teachers.
Keywords: chemistry; visualization elements; information and communication technology (ICT); learning and teaching